Micronutrients, their potential effect on patients with systemic sclerosis. Issue 5 (September 2014) - Wan, Ya-Nan; Yan, Jun-Wei; Peng, Wen-Jia; Zhang, Jun-Qing; Xiao, Chang-Chun; Wang, Bing-Xiang; Wang, Jing
Abstract Over the past years, several evidences have supported an important role of specific micronutrients, including vitamin A, vitamin D and vitamin E in immune dysfunction, vascular involvement and fibrotic changes involved in systemic sclerosis (SSc) development. In PubMed, eight clinical trials about the therapy of micronutrients on SSc patients were searched out using medical subject headings terms (SSc: "scleroderma, localized", "scleroderma, systemic", "scleroderma, diffuse" and "scleroderma, limited"; vitamins "vitamin A", "thiamin", "riboflavin", "niacin", "pantothenic acid", "vitamin B 6", "biotin", "folic acid", "vitamin B 12", "inositol", "choline", "ascorbic acid", "vitamin D", "vitamin E", "tocopherols", "vitamin K" and "vitamin P"; and minerals: "calcium", "magnesium", "potassium", "sodium", "phosphorus", "sulfur", "chlorine", "iron", "copper", "iodine", "zinc", "selenium", "manganese", "molybdenum", "cobalt", "chromium", "tin", "vanadium", "silicon", "nickel" and "fluorine"). This brief review will summarize current understanding on that for the further prospect of future studies. Though the clinical trials for the treatment of SSc with micronutrients are still in their infancy, more researches are needed to substantiate the current results and accelerate the knowledge in this field.